At home with my baby. Child care in professional urban sectors (Estudios Sociales, 2021)
The paper studies the care of children less than a 1 year in professional sectors of the City of Buenos Aires. The activities, interactions and feelings observed in four hours of care between a mother and her 11-month-old baby are analyzed in the context of a series of interviews carried out with mothers and fathers of this socioeconomic stratum. The project is part of the social studies of care and the sociology of emotions, fields that have sought to better understand the motivations and experiences of social actors in their affective practices with others. The main hypothesis is that the dynamics and rhythms of care in these sector can assume unique temporal arrangements, linked to simultaneity, alternation, continuous bonding and permanent availability among children and their caregivers.
Keywords: emotions; early infancy; childreading; care; profesionalization